Improvement of the service life of sustainable self-compacting concrete SCC by integrating high dosage of cement replacement - Mohammed, K. Mahmoud; Dawson, Andrew; Thom, Nicholas (Institute of Research Engineers and Doctors, 2015)
Based on simple diffusion theory and a timedependent factor (α) for the chloride diffusion coefficient, chloride penetration through concrete was numerically modelled and the service life was predicted. This was done for two reference mixes (normal vibrated concrete, NVC and selfcompacting concrete, SCC) and three other types of sustainable SCC incorporating high levels of cement replacement. All the mixes have a design compressive strength of 50-60 MPa at 28 days with different types of binders. In this study, the non-steady state chloride diffusion coefficients (Dnss) and the surface chloride concentrations (CS), which are mainly used for the numerical modelling of the chloride penetration phenomena, were calculated according to the recommendations of Nordtest methods NT BUILD 443 with the aid of using a developed excel solver tool. The numerical results indicated that the NVC at the same design strength level of the reference SCC showed lower service life and higher depth of cover design. For the sustainable SCC, the results showed that the incorporation of relatively high partial replacement of fly ash (FA) Class F and the combined high partial replacement of FA with the silica fume (SF) has little effect on the penetration parameter (Kcr) relative to that of reference-SCC. However, the incorporating of limestone powder (LP) at the same cement replacement ratio as other admixtures increased the Kcr, reduced the service life and increased the depth of cover design even when compared to the NVC at the same strength level.